Splenic vasculitis, thrombosis, and infarction in a febrile dog infected with Bartonella henselae. (26th August 2015) - Friedenberg, Steven G.; Balakrishnan, Nandhakumar; Guillaumin, Julien; Cooper, Edward S.; Lewis, Kristin; Russell, Duncan S.; Breitschwerdt, Edward B.
Abstract: Objective: To describe the clinical course and successful management of a febrile dog with polyarthritis, splenic vasculitis, thrombosis, and infarction that was infected with Bartonella henselae . Case Summary: An 8‐year‐old female spayed Labrador Retriever was referred to The Ohio State University Veterinary Medical Center Emergency Service for evaluation of limping, fever, vomiting, and malaise of 4 days' duration. Physical examination abnormalities included generalized weakness, diminished conscious proprioception, bilateral temporalis muscle atrophy, and diarrhea. Peripheral lymph nodes were normal, and there were no signs of abdominal organomegaly, joint effusion, or spinal pain. Abdominal ultrasound identified a nonocclusive splenic vein thrombus. Fine‐needle aspirates of the spleen revealed pyogranulomatous inflammation, mild reactive lymphoid hyperplasia, and mild extramedullary hematopoiesis. Splenic histopathology found marked, multifocal to coalescing acute coagulation necrosis (splenic infarctions) and fibrinoid necrotizing vasculitis. Bartonella henselae DNA was amplified by polymerase chain reaction and sequenced from the splenic tissue. The dog responded favorably to antimicrobials and was healthy at the time of follow‐up evaluation. New and Unique Information Provided: Bartonella henselae is an incompletely characterized emerging canine pathogen. This case report establishes a potential role for this bacterium as a cause of vasculitis and thromboembolism, which have not been previously reported in association with B. henselae infection in dogs.